v^2-36=

Simple and best practice solution for v^2-36= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for v^2-36= equation:


Simplifying
v2 + -36 = 0

Reorder the terms:
-36 + v2 = 0

Solving
-36 + v2 = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + v2 = 0 + 36

Combine like terms: -36 + 36 = 0
0 + v2 = 0 + 36
v2 = 0 + 36

Combine like terms: 0 + 36 = 36
v2 = 36

Simplifying
v2 = 36

Take the square root of each side:
v = {-6, 6}

You can always share this solution

See similar equations:

| 24uxy^5-22u^5y^5= | | 4u^6+6u^5-10u^4= | | 10x^2+12x+18=0 | | 25p^2=4 | | 5x^2=13x+6 | | x^2+10x+25=0 | | X^2+4x+4=0 | | x^2+6x+9=0 | | -4x=2x^2-6 | | -x=2x^2-6 | | -2x=3x^2-1 | | -9x=2x^2-5 | | x^2-5x-6=0 | | x^2-x-12=0 | | 3x^2+5x-13=11-9x | | 5x^3-5x=0 | | 16x^2+2x-3=0 | | 4x^2-25=0 | | x^2-19x=0 | | x^2-x+18=0 | | 13x^2-11x=0 | | 7x^2+4x-15=49-44x | | 3x^3+9x^2+6x=0 | | x^2-3x-18=0 | | x^2-63x+60=0 | | 2x(4x-7)+3=(2x-7)(3x+4)+2x^2 | | 8x^3+10xy+6x^2y^5=0 | | 2X(X^2-4X+7)= | | 2x^2-5x-5=0 | | 2x^2-38x=7x^2-3x-24 | | 9p^2+18p=10 | | x^2-5x=6 |

Equations solver categories